USING KALBEK PRODUCTS (USED CALENDAR) TO IMPROVE STUDENT LEARNING OUTCOMES ON FPB AND KPK TOPICS IN CLASS IV SDN 3 TAROK - Afrizal; Siti Mayang Sari; Akmaluddin (International Conference on Education, Science, Technology and Health (ICONESTH), 2023)
This research aims to analyze the increase in student learning outcomes after using kalbek teaching aids on the topics of FPB and KPK in class IV SDN 3 Tarok. This research was classroom action research consisting of two cycles. Each cycle had four stages, namely: planning, implementation, observation, and reflection. The research was carried out at SDN 3 Tarok, Meukek District, and South Aceh Regency for 2 months in the 2023/2024 academic year. The subjects of this research were 14 fourth grade students consisting of 7 male students and 7 female students. The instruments used were formative tests and observation sheets. Data analysis used descriptive statistics based on the results of formative tests and observation sheets for each cycle. The results of the research showed that the use of kalbek teaching aids can improve student learning outcomes as indicated by an increase in the completeness of student learning outcomes from cycle I to cycle II, namely cycle I (64.29%) and cycle II (92.86%). Student activity in learning also increased from cycle I, 53.6% to 85.7% in cycle II.